Investigation of Mixtures of BF3 Carbonates and LiX (X = OCH2CF3, OC(H)(CF3)2, CO2CF3) as Novel Electrolyte Systems for Lithium Ion Batteries. Issue 8 (21st April 2020) - Eisele, Lea; Laszczynski, Nina; Görg, Marius; Schneider, Marius; Burger, Stephan; Radkte, Valentin; Lucht, Brett; Krossing, Ingo
Abstract : The stoichiometric 1:1 combination of LiX (X = OCH2 CF3, OC(H)(CF3 )2, CO2 CF3 ) with BF3 ·D (D = dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, propylene carbonate and diethyl ether) yields an electrolyte with a significantly increased conductivity in comparison to pure LiX in EC:EMC (3:7 wt%). The combination of Li[CO2 CF3 ] and BF3 ·EC displays with 5.8 mS·cm –1 (1.5 mol·L –1 ) the highest conductivity of all investigated systems, which is also higher than that of LiBF4 in the same solvent. NMR studies of all composite electrolytes show the presence of various boron species like BX3, Li[BF3 X], Li[BF2 X2 ] and Li[BFX3 ], which distribute characteristically for each LiX. The investigation of the electrochemical behavior of the composite electrolytes in Li[Ni0.33 Mn0.33 Co0.33 O2 ]/graphite cells showed a direct relation between cycling behavior, impedance and boron content on CEI/SEI. In the differential plots of the first cycle, an irreversible oxidation was observed in all cells, which is attributed to the formation of the SEI of the composite electrolyte. Ex situ analysis of the electrodes with XPS showed an increase of the boron content on the surface of both electrodes in the order of Li[OC(H)(CF3 )2 ] < Li[OCH2 CF3 ] < Li[CO2 CF3 ]. This ordering was also found for the growth of the impedance of the cells.